Comparison of Persian Simple Vowels Production in Cochlear Implanted Children Based on Implantation Age - Peiman Zamani; Naeimeh Daneshmandan; Abolfazl Salehi; Mehdi Rahgozar (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: Age at implantation is one of the most important factors in improving speech and language skills in children with cochlear implants. Moreover, good vowel articulation is very important in the speech. So, the purpose of this research was to determine whether age at cochlear implantation influences the production of Persian simple vowels when cochlear implantation is undertaken below the age of 2 years as compared with cochlear implantation later in life. Materials & Methods: This research was a comparative and cross-sectional study. Based on inclusive and exclusive criteria (i.e., have physical and mental health, monolingual or bilingual, have 9±1 months post-surgery rehabilitation, no hearing handicapped parents and no medical problems history), 140 children who cochlear implanted in Amir-Alam and Hazrate Rasool hospital of Tehran city were selected by convenient sampling and assigned to two groups, children implanted under the age of 2 years and those implanted above the age of 2 years Also 238 normally hearing children were selected for control group by randomized sampling. The first and second formant frequency (F1 & F2) of the Persian simple vowels /i, e, æ, a, o, u/ were evaluated by the version of 1.2 of SFSwin software. Data were analyzed by Independent T test. Results: The findings indicated that there were significant differences between two groups in the mean of F2/i/ (P=0.046), F1/e/ (P=0.011), F2/e/ (P=0.005), F2/æ/ (P=0.039), F2/a/ (P=0.012), F2/o/ (P=0.012) and F2/u/ (P=0.006), but there was no significant difference between then in the mean of F1/i/, F1/æ/, F2/a/, F1/o/, F1/u/ (P>0.05). According to these results, no significant difference was seen between normal group and children who received their cochlear implants under the age of 2 years in the mean of variables (P>0.05). Conclusion: Observing significant differences in the quality of the production of Persian simple vowels between children implanted under the age of 2 years and children who received their implants after the age of 2 years, and no significant differences between children who implanted before 2 years of age and normally hearing children is in the favor of the positive effect of early cochlear implantation on speech sound development. Also, the results indicate that when performed under the ages of 2 years, cochlear implantation can prevent from vowels distortions in the speech flow of the receivers.